Breaking Barriers: Sustainability of Legal Reforms in Women's Property Rights in Nepal - Budhathoki, Drona (International Research Journal of MMC, 2025)
Women's property rights refer to the legal rights women have to own, inherit, and control property, ensuring equal access to assets and resources. These rights help promote gender equality and economic independence for women. The primary objective of this study is to examine the recent legal reforms in Nepal aimed at promoting women's property ownership and evaluate their sustainability. This study employed an explanatory research design to investigate how Nepali laws facilitate women’s property ownership. Data was collected in two ways: by analyzing current laws and interviewing seven experts in politics and law, including those involved in creating and enforcing these laws. The study used purposive sampling to select these participants. Article 25 of Nepal’s Constitution (2015) and the Civil Code (2017) guarantee women the right to acquire, own, use, sell, and transfer property. Daughters have equal rights to family and ancestral property, while widows can claim and separate their share. Married women can dissolve marital ties and claim property, and husbands must provide support. Various laws, like the Right to Equality and Free Education Act, the Domestic Violence Act, the Sexual Harassment Prevention Act, the Human Trafficking Control Act, and others, aim to safeguard women’s rights. However, effective implementation needs women’s access to education, legal awareness, and leadership roles. Changing negative attitudes toward daughters and maintaining family unity are also vital for sustaining these legal protections and ensuring real equality. In conclusion, Nepal's legal landscape has undergone significant evolution toward gender equality, particularly in property rights, through key reforms such as the Constitution of Nepal (2015) and the National Civil Code (2017). These legal advancements ensure equal inheritance rights for both daughters and sons, dismantling patriarchal norms that historically marginalized women. The Supreme Court's rulings and the influence of international frameworks like the Beijing Declaration further reinforce the importance of gender equality in property ownership. Collectively, these developments foster a more inclusive, just, and economically empowered society for women in Nepal. In Nepal, women's property rights promote gender equality by ensuring women have equal access to inheritance and ownership, contributing to their economic empowerment. However, cultural and societal barriers still limit the full realization of these rights in many areas. This statement implies that women’s property rights are essential for promoting gender equality and economic independence. In Nepal, legal reforms like the Constitution of 2015 and the Civil Code of 2017 grant women equal rights to own and inherit property. However, social attitudes and a lack of legal awareness still limit their full implementation. Education, leadership opportunities, and societal change are vital for ensuring sustainable property rights and real equality for Nepali women.